A room with a view - Forster, E. M. (Edward Morgan) 1879-1970.; Pierce-Roberts, Tony.; Merchant Ivory Productions; Goldcrest Films International; National Film Finance Corporation (Great Britain).; Curzon Film Distributors; Film Four International; BBC Video (Firm).; Warner Home Video (Firm).; BBC Worldwide Americas, Inc. ([England] BBC Video Burbank, Calif. Distributed in the USA and Canada by Warner Home Video, 2003)
Set in the early 1900's. "[The film] tells the story of the coming of age of Lucy Honeychurch (Helena Bonham-Carter). Longing to burst free from the repression of British upper class manners and mores, she must wrestle with her inner romantic longings to choose between the passionate George (Julian Sands) and the priggish but socially suitable Cecil (Daniel Day-Lewis)"--Container.
Based on the novel by E.M. Forster.
Originally released as a motion picture in 1985.
New restoration of film ; digitally remastered sountrack.
Cinematography, Tony Pierce-Roberts ; music, Richard Robbins ; editor, Humphrey Dixon.
Maggie Smith, Helena Bonham-Carter, Denholm Elliott, Julian Sands, Simon Callow, Patrick Godfrey, Judi Dench, Fabia Drake, Joan Henley, Amanda Walker, Daniel Day-Lewis, Maria Britneva, Rosemary Leach, Rupert Graves, Peter Cellier, Mia Fothergill.
DVD videos.
Keywords: Forster, E. M. -- 1879-1970 -- Film adaptations; British -- Italy -- Drama; Young women -- Drama; Love -- Drama; Man-woman relationships -- Drama; Social classes -- Great Britain -- Drama; Florence (Italy) -- Drama; Film adaptations; Video recordings for the hearing impaired